Finite element modelling of the oxidation kinetics of Zircaloy-4 with a controlled metal-oxide interface and the influence of growth stress. (November 2015) - Zumpicchiat, Guillaume; Pascal, Serge; Tupin, Marc; Berdin-Méric, Clotilde
Highlights: We developed two finite element models of zirconium-based alloy oxidation using the CEA Cast3M code to simulate the oxidation kinetics of Zircaloy-4: the diffuse interface model and the sharp interface model. We also studied the effect of stresses on the oxidation kinetics. The main results are: Both models lead to parabolic oxidation kinetics in agreement with the Wagner's theory. The modellings enable to calculate the stress distribution in the oxide as well as in the metal. A strong effect of the hydrostatic stress on the oxidation kinetics has been evidenced. The stress gradient effect changes the parabolic kinetics into a sub-parabolic law closer to the experimental kinetics because of the stress gradient itself, but also because of the growth stress increase with the oxide thickness. Abstract: Experimentally, zirconium-based alloys oxidation kinetics is sub-parabolic, by contrast with the Wagner theory which predicts a parabolic kinetics. Two finite element models have been developed to simulate this phenomenon: the diffuse interface model and the sharp interface model. Both simulate parabolic oxidation kinetics. The growth stress effects on oxygen diffusion are studied to try to explain the gap between theory and experience. Taking into account the influence of the hydrostatic stress and its gradient into the oxygen flux expression, sub-parabolic oxidation kinetics have been simulated. The sub-parabolic behaviour of the oxidation kinetics can be explained by a non-uniform compressive stress level into the oxide layer.